Multiparametric Quantitative Brain MRI in Neurological and Hepatic Forms of Wilson's Disease. Issue 6 (11th November 2019) - Dezortova, Monika; Lescinskij, Artem; Dusek, Petr; Herynek, Vit; Acosta‐Cabronero, Julio; Bruha, Radan; Jiru, Filip; Robinson, Simon D.; Hajek, Milan
Abstract : Background: In Wilson's disease (WD), demyelination, rarefaction, gliosis, and iron accumulation in the deep gray matter cause opposing effects on T2 ‐weighted MR signal. However, the degree and interplay of these changes in chronically treated WD patients has not been quantitatively studied. Purpose: To compare differences in brain multiparametric mapping between controls and chronically treated WD patients with neurological (neuro‐WD) and hepatic (hep‐WD) forms to infer the nature of residual WD neuropathology. Study Type: Cross‐sectional. Population/Subjects: Thirty‐eight WD patients (28 neuro‐WD, 10 hep‐WD); 26 healthy controls. Field Strength/Sequence: 3.0T: susceptibility, T2 *, T2, T1 relaxometry; 1.5T: T2, T1 relaxometry. Assessment: The following 3D regions of interest (ROIs) were manually segmented: globus pallidus, putamen, caudate nucleus, and thalamus. Mean bulk magnetic susceptibility, T2 *, T2, and T1 relaxation times were calculated for each ROI. Statistical Tests: The effect of group (neuro‐WD, hep‐WD, controls) and age was assessed using a generalized least squares model with different variance for each ROI and quantitative parameter. A general linear hypothesis test with Tukey adjustment was used for post‐hoc between‐group analysis; P  < 0.05 was considered significant. Results: Susceptibility values were higher in all ROIs in neuro‐WD compared to controls and hep‐WD ( P  < 0.001). In basal ganglia, lower T2 and T2 * were found in neuro‐WD compared to controls ( P  < 0.01) and hep‐WD ( P  < 0.05) at 3.0T. Much smaller intergroup differences for T2 in basal ganglia were observed at 1.5T compared to 3.0T. In the thalamus, increased susceptibility in neuro‐WD was accompanied by increased T1 at both field strengths ( P  < 0.001 to both groups), and an increased T2 at 1.5T only ( P  < 0.001 to both groups). Data Conclusion: We observed significant residual brain MRI abnormalities in neuro‐WD but not in hep‐WD patients on chronic anticopper treatment. Patterns of changes were suggestive of iron accumulation in the basal ganglia and demyelination in the thalamus; 3.0T was more sensitive for detection of the former and 1.5T of the latter abnormality. Level of Evidence: 2 Technical Efficacy Stage: 3 J. Magn. Reson. Imaging 2020;51:1829–1835.